Selected works of D.T. Suzuki. - Jaffe, Richard M., 1954- (University of California Press, 2015)
Daisetsu Teitaro Suzuki was a key figure in the introduction of Buddhism to the non-Asian world. Many outside of Japan encountered Buddhism for the first time through his writings and teaching, and for nearly a century his work and legacy have contributed to the ongoing religious and cultural interchange between Japan and the rest of the world, particularly the United States and Europe. Selected Works of D.T. Suzuki gathers the full range of Suzuki's writings-both classic essays and lesser-known but equally significant articles. This first volume in the series presents a collection of Suzuki'